Dose and time-dependent acute and subchronic oral toxicity study of propoxazepam in mice and rats - Yakovlevich Golovenko, Nikolay; Nikolayevna Kovalenko, Valentina; Borisovich Larionov, Vitalii; Semenovich Reder, Ðnatoliy (International Journal of Pharmacology and Toxicology, 2020)
Propoxazepam, 7-bromo-5 - (o-chlorophenyl)-3-propoxy - 1,2-dihydro - 3H-1,4-benzodiazepin-2-one, in the models of nociceptive and neuropathic pain showed significant analgesic activity. In order to explore clinical potential of propoxazepam for long term human consumption, toxicology testing in laboratory animals using well-accepted international guidelines is required. Acute toxicity tests were conducted by the oral administration of 2500; 3500; 4000; 4500 and 5000 mg/kg body weight to male and female mice and rats for a period of 3, 7 and 14 day. In subacute study, male rats were administered with various doses of propoxazepam (0.9, 4.5, and 9.0 mg/kg) to evaluate its toxicity for a period of 90 days. The effect of propoxazepam on body weight gain and organ weights, food and water consumptions were analyzed. From the present study, it can be concluded that the acute (3, 7 and 14 days) and subchronic (90 days) oral administrations of propoxazepam did not produce any clinical signs of toxicity or mortality of the male and female mice and rats. These results revealed that the LD50 of propoxazepam is greater than 5000 mg/kg and it therefore, belongs to the category V of relatively non-toxic substances according to the GHS. In the acute toxicity study, neither mortality no significant change in the body weight and the relative organ weights were recorded in all treated mice and rats. Present data set revealed that there wasn`t a strong correlation between body weight with food and water consumptions. The result indicates that the oral administration of propoxazepam did not produce any significant toxic effect in mice and rats and the substance can be safely used for therapeutic use in pharmaceutical formulations.Â Â